Analisis Sosial Terhadap Fenomena Mahasiswa Pekerja Studi Universitas Negeri Makassar - Tahir, Muhammad Imran; Kamaruddin, Syamsu A; ., Najamuddin (Equilibrium: Jurnal Pendidikan, 2025)
This study aims to determine: 1) the social motives of UNM students who study while working, 2) the social orientation of UNM students who study while working, and 3) the relationship between social motives and social orientation of UNM students who study while working. This research uses a qualitative descriptive approach with a case study method. The study is directed at describing the conditions or phenomena of UNM students who study while working, the social orientation of these students, and the relationship between their social motives and social orientation. The technique used to determine informants is purposive sampling, with a total of 15 informants. Data collection techniques include observation, interviews, and documentation. Data validity was ensured through triangulation of sources, time, and techniques. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings of this research reveal that the social motives of UNM students who study while working consist of four primary factors: economic needs, the desire to become more independent, the aim to enrich their experiences, and the intention to build social relationships. In terms of social orientation, these students tend to prioritize relationships in the workplace, experience limited participation in campus activities, and maintain social relationships with their families and friends. Furthermore, the study finds a clear relationship between social motives and social orientation: economic motives encourage students to prioritize work-related social relationships; the desire to gain work experience often leads to decreased involvement in campus life; and the pursuit of independence motivates students to form social networks that support their future careers.